ACCOMMODATION STRATEGY FOR COMMUNICATION OF EASTERN ETHNIC STUDENTS WITH JAVANESE ETHNICITY IN SURAKARTA - Vita, Nurul Kawuri Sae; Ramadhani, Oktavia Rizky Karunia; Najah, Ghaida Shafa; Rahmadani, Bernadheta Nadila Dea; Utami, Evita Putri; Kartinawati, Erwin (Universitas Dharmawangsa Medan, 2025)
Differences in cultural backgrounds often create obstacles in the process of interaction between individuals. This study discusses the case of interaction between students of ethnic groups from eastern Indonesia and students of Javanese ethnicity in the Surakarta campus environment. The presence of students from eastern Indonesia in the context of higher education in Java creates a complex intercultural meeting space. Differences in values, norms, and communication styles between these two ethnic groups often create barriers to building social relationships. This study aims to identify the forms of communication accommodation strategies employed by both parties in their efforts to build effective communication. The approach used is a phenomenological approach to explore the direct experiences of informants in the process of cross-cultural interaction. The theory used is Communication Accommodation Theory to analyze how individuals adapt their communication styles to achieve mutual understanding. Data collection techniques were conducted through in-depth interviews with three student informants from the eastern region and one Javanese ethnic student informant. The results of the study indicate that the most dominant communication barriers manifested in the form of differences in language style, perceptions of emotional expressions, and cultural stereotypes. The accommodation strategies employed include convergence by Eastern students as a form of adaptation to the majority culture, and divergence in the context of preserving cultural identity.